Energy efficiency of non-face brick production with particular reference to the drying process - de la Hunt, Herbert William Garnet (Department of Mechanical Engineering, 2023)
Energy inefficiencies are at present a characteristic of the Heavy Clay Industry throughout the world. In the Western Cape there has been a marked trend towards the use of unsophisticated plant for the manufacture of non-face plaster bricks since the nineteen sixties. At present all non-face plaster bricks are fired in clamps and only a few factories use dryers. Hollow ware rather than solid bricks find favour in South America, Asia and Europe, with the exceptions of the United Kingdom and the Netherlands, (the Netherlands use the soft mud process which does not lend itself to hollow ware production). However, in South Africa, in spite of potential energy and clay saving, the number of hollow block factories, has shrunk in the past 30 years. The only move towards hollow ware, has been the perforation, of face bricks. In the Western Cape no factories perforate their non-face bricks. The reduced production and cartage costs, could be passed on to the builder. Other advantages for low-cost housing are easier bricklaying, as well the aesthetic appeal of clay for semi-face finishes. Of considerable concern, to the Heavy Clay Industry is the fact that the energy and clay saving, as well as the reduced cartage cost, allows the clay hollow block to be competitive against cement, it's major rival in the field of "affordable housing". The hollow block, although larger, can be lighter than the solid brick, and has the further advantages of less units per square metre "in the wall", as well as good insulating properties. To produce hollow ware in the Western Cape, without major plant changes, it was necessary to test the possibility of firing hollow ware in clamps. This was achieved for the conventional non-face brick size and the maxi brick, both made with transverse holes. The purpose of this study was to provide an efficient method of drying bricks, particularly for factories which were drying in the open air. The hollow ware possibility widened the scope of the study, and a dryer was designed to dry both hollow ware and solid bricks. A constraint on the dryer design was the basic premise that the dryer would ultimately form part of an integrated dryer/kiln system. Open air drying in the Western Cape, while requiring no additional heat or electrical energy, does use forklifts, which use diesel and are expensive. The open air drying process has a high waste component and is weather dependent. Heavy losses have been experienced, not only during the autumn and spring, but often even in the middle of summer, due to unseasonal downpours. Arguably the main area of concern, to the producer, is the inefficient use of plant and labour during the winter months. The costs, to the producer, of the open air drying process were established. The literature survey dealt with the basic principles and problems of drying heavy clay products, as well as innovations and engineering problems in the field of drying. Initial tests were done on a test unit, large enough to simulate plant conditions. From the results of these tests, the work covered in the literature, as well as past practical plant experience, sufficient information was available to build a prototype plant dryer. The prototype dryer was constructed to dry units standing "one-high, soldier". With this setting, and the proposed airflow, it is possible to treat each unit in exactly the same manner as its neighbour. In this way it is possible to obtain results comparable to those obtained under laboratory conditions and achieve fast drying times. Fast drying implies a relatively small dryer with minimum heat losses, as well as having good control. The "One-high" configuration lends itself to simple setting and off-loading mechanisms. An objective of this study was to minimise the capital investment. The value of the waste saving, on open air drying, over two years, was regarded as an arbitrary amount to aim for, as the cost of the dryer. In fact, the dryer was built at below the capital cost of the forklifts which were eliminated by changing the drying method. Pallets were eliminated, as was the need for setting labour. Fast drying of the order of 1-3 hours implies that the dryer is, in a sense, an extension of the extrusion process. The dryer can be switched on and off with the extruder, but what is more important is the fact that a plant which normally operates only on day shift, can be operated on a 24 hour basis without the need to build extra drying facilities. This latter point is of considerable importance in building boom periods. Clamps do not generate recoverable waste heat for drying. Phase two of this project will be to design the kiln, which is compatible, in concept, with the dryer. The proposed kiln will operate with less specific energy than clamps and generate the heat required to dry the bricks. In conclusion, the study leaves the fine tuning of the dryer for energy efficiency, still to be completed. In spite of this the dryer satisfies all the proposed conceptual criteria. It will be able to operate on the waste hot air from the kiln. If the kiln can operate at the level of the best commercial kilns at present available, and yet be built for a capital amount of the same order as the dryer, then an attractive alternative to clamp firing will have been found. Because the recoverable heat from the kiln is available, irrespective of the drying process, there will be no specific energy drying cost, the same situation that applies with open air drying, but, with none of its attendant problems.